AGGREGATE DEMAND, NAIRU AND ECONOMIC GROWTH IN INDONESIA - Zulviana Setya Ningrum; Indraswati TA Reviane; Nur Dwiana Sari Saudi (SEAN Institute, 2022)
This study aims to determine the effect of aggregate demand on economic growth either directly or indirectly through NAIRU in Indonesia. The analysis model used in this research is path analysis, using time series data for the period 1997-2021. As for the results of the study, namely investment directly has a negative and insignificant effect on economic growth and indirectly has a negative and significant effect through NAIRU. Consumption directly has a positive and insignificant effect on economic growth and indirectly has a negative and significant effect through NAIRU. Government spending directly has a positive and insignificant effect on economic growth and indirectly has a positive and significant effect through NAIRU.